2016
DOI: 10.3389/fphys.2016.00636
|View full text |Cite|
|
Sign up to set email alerts
|

FVB/NJ Mice Are a Useful Model for Examining Cardiac Adaptations to Treadmill Exercise

Abstract: Mice are commonly used to examine the mechanisms by which exercise improves cardiometabolic health; however, exercise compliance and adaptations are often strain-dependent or are variable due to inconsistency in exercise training protocols. In this study, we examined nocturnal/diurnal behavior, treadmill exercise compliance, and systemic as well as cardiac-specific exercise adaptations in two commonly used mouse strains, C57BL/6J, and FVB/NJ mice. Metabolic cage analysis indicated a strong nocturnal nature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 67 publications
(90 reference statements)
4
39
0
Order By: Relevance
“…Conversely, several strains showed significant increases in endurance exercise capacity with training (129S1, CE/J, FVB/NJ, NOD/ShiLtJ, PL/J, SJL/J, and SWR/J). We, and others previously reported that FVB/NJ mice exhibit significant improvements in performance with exercise training (Massett and Berk, 2005 ; Chow et al, 2007 ; Massett et al, 2009 ; Gibb et al, 2016 ). Those changes in endurance exercise capacity were associated with physiological changes consistent with the expected cardiovascular and metabolic adaptations to training (Massett and Berk, 2005 ; Chow et al, 2007 ; Gibb et al, 2016 ), indicating this strain is useful for genetic and physiological studies of exercise training responses.…”
Section: Discussionmentioning
confidence: 64%
“…Conversely, several strains showed significant increases in endurance exercise capacity with training (129S1, CE/J, FVB/NJ, NOD/ShiLtJ, PL/J, SJL/J, and SWR/J). We, and others previously reported that FVB/NJ mice exhibit significant improvements in performance with exercise training (Massett and Berk, 2005 ; Chow et al, 2007 ; Massett et al, 2009 ; Gibb et al, 2016 ). Those changes in endurance exercise capacity were associated with physiological changes consistent with the expected cardiovascular and metabolic adaptations to training (Massett and Berk, 2005 ; Chow et al, 2007 ; Gibb et al, 2016 ), indicating this strain is useful for genetic and physiological studies of exercise training responses.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, it has been previously presented in two HCM mouse models that mice expressing tropomyosin (Tm-E180G) developed a more pronounced hypertrophic phenotype in FVB/N than in C57BL/6 genetic background (Prabhakar et al, 2001;Michele et al, 2002), and in mice with a mutation in actin (ACTZ E99K), the probability of sudden cardiac death was almost completely eliminated in mice bred on C57/BL6 background (Rowlands et al, 2017). The importance of the mouse genetic background on the basal cardiac function, adaptations to exercise, or stress is also well-documented (Barnabei et al, 2010;Peng et al, 2011;Gibb et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…All studies began at 15 weeks of age; food and water were provided ad libitum; and the mice were maintained on a 12:12-h light-dark schedule, as described previously. 63 At the conclusion of animal experiments, and following a 6 h fast, mice were On the Friday immediately following treadmill familiarization, we subjected mice to an exercise capacity test. For this, the mice were acclimated to the treadmill for 10 min, with the speed and incline set initially to zero.…”
Section: Methodsmentioning
confidence: 99%
“…60 The most common metabolic adaptation of the heart to exercise is mitochondrial biogenesis. [61][62][63] While various signaling events likely lead to an increase in mitochondrial mass, exercise-induced increases in peroxisome proliferator-activated receptor coactivator 1α (PGC-1α) play a critical role. 64 Interestingly, induction of PGC-1α in response to exercise was prevented in IGF1r knockout mice, and it has been shown that signaling through PI3K, but not AKT, is required for this biogenic response.…”
Section: ) Additional Effectors Of Physiologic Cardiac Growth: Severmentioning
confidence: 99%
See 1 more Smart Citation